A Case of Primary tuberculosis of the tongue mimicking malignancy (Bangladesh Journal of Otorhinolaryngology, 2020)
Tuberculosis of the tongue is a very rare event even in a areas and countries in which tuberculosis is endemic. The disease can present itself in a variety of clinical appearances, most of which may mimic malignant lingual neoplasm’s clinically. Here we report a case of lingual non healing ulcer in a 44 years female which was clinically suspected as malignant ulcer. The diagnosis of lingual tuberculosis was made by histopathology.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 199-202